Flagellin modulates TIM4 expression in mast cells. (15th July 2014) - Li, Linjing; Mo, Lihua; Hao, Huijie; Yang, Wanhe; Zhou, Quanbo; Xue, Fumin; Shi, Zhaoyang; Liu, Zhigang; Yang, Ping‐Chang; Feng, Baisui
Abstract T‐helper (Th) 2 polarization functions in a number of immune diseases, but their pathogenesis needs further investigation. Some microbial products or components are strong adjuvants in the creation of mouse models of Th2 polarization. T cell immunoglobulin mucin molecule (TIM) 4 is a facilitator in the initiation of Th2 response. This study looks at the role of one of the microbial products, flagellin (FGN), in the induction of TIM4 expression in mast cells. Bone marrow derived mast cells (BMMC) were generated. Induction of TIM4 in mast cells was assessed in both experiments in vitro and in vivo. The signal transducer and activator of transcription 6 (Stat6) phosphorylation in BMMC were assessed by Western blotting. A coculture model with FGN‐primed BMMC and naïve CD4+ T cells was employed to assess FGN in facilitating the expression of TIM4 in mast cells. After exposure to FGN, TIM4 levels were significantly increased in BMMC and mast cells of the mouse intestine, which was accompanied by increased STAT6 phosphorylation. Culture with FGN‐primed BMMC, naïve CD4+ T cells developed into Th2 cells by a TIM4‐dependent manner. We conclude that FGN can induce mast cells to express TIM4, which helps initiate Th2 polarization.